Neoliberalism and precarious work in nursing in the COVID-19 pandemic: repercussions on mental health - Rezio, Larissa de Almeida; Oliveira, Elda de; Queiroz, Aline Macêdo; Sousa, Anderson Reis de; Zerbetto, Sonia Regina; Marcheti, Priscila Maria; Nasi, Cíntia; Nóbrega, Maria do Perpétuo S. S. (Revista da Escola de Enfermagem da USP, 2022)
Objective: to understand how the contradictions and tensions of neoliberal policy, materialized in precarious work, affect nursing workers’ mental health in the context of the COVID-19 pandemic. Method: this is a study with a qualitative and descriptive approach, analyzed in the light of neoliberal economic policy. Data were collected through virtual means, with the participation of 719 nursing workers, from April to June 2020. To organize the data, the IRaMuTeQ® software and thematic analysis were used. Results: the reports revealed the lack of value of workers and the loss of social labor rights; the progressive nature of the neoliberal policy, its threats and repercussions on workers’ mental health; and recognition by female workers that political and class participation does not occur in isolation, but collectively. Conclusion: under the aegis of neoliberal policy, the COVID-19 pandemic brought an upsurge precarious work, influencing nursing workers’ subjectivity and mental health.